Multicriteria optimization as enabler for Sustainable Ceramic Matrix Composites. Issue 6 (12th September 2022) - Schneider, Tobias; Wietschel, Lars; Schüppel, Denny; Riesner, Jonas; Konrad, Kevin; Thorenz, Andrea; Tuma, Axel; Koch, Dietmar
Abstract: Over the past 40 years, development of Ceramic Matrix Composites (CMCs) has focused mainly on the improvement of material performance and optimization of cost‐efficient production routes. Recently, more fields of application have opened up for CMCs, in which environmental impacts are relevant. These impacts have barely been investigated so far but receive growing interest due to increasing awareness of the environmental consequences. Our innovative approach frames material properties in relation to environmental impacts (e.g., global warming potential in CO2 emission) by varying process parameters to balance optimum performance against environmental considerations. First, the process of wet filament winding has been investigated up to the Carbon Fiber Reinforced Plastic (CFRP) state by changing both the curing and tempering temperatures. During the production of CFRP plates, mass and energy flows were tracked in each step. Three point‐bending and interlaminar shear tests have been performed on the resulting samples to identify basic mechanical properties. The environmental impacts are determined by a cradle‐to‐gate Life Cycle Assessment (LCA), using the software SimaPro. The resulting tradeoffs between mechanical properties and environmental impacts show nonlinear behavior, thus revealing optimum points above which improved mechanical properties are associated with significantly higher CO2 emissions. Abstract : Simplified outline of the research approach for the development of Sustainable Ceramic Matrix Composites (SCMCs).